2000
DOI: 10.1021/ma9918452
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the C−O−Bond Homolysis of Trialkylhydroxylamines

Abstract: Trialkylhydroxylamines and persistent nitroxide radicals are important regulators of living radical polymerizations. Since the polymerization times decrease with increasing rate of the C−O-bond dissociation between the polymer chain and the nitroxide moiety, the factors influencing the homolysis rate constants are of considerable interest. Here, data are presented for 27 model trialkylhydroxylamines in solution containing TMIO, TEMPO, TEDIO, TIPNO, DBNO, SG1, and similar nitroxide groups and primary, secondary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

35
354
6

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 256 publications
(398 citation statements)
references
References 59 publications
(81 reference statements)
35
354
6
Order By: Relevance
“…SG1-base initiators such as BlocBuilder have lower activation energy and much higher dissociation rate constant (k d ) compared to TEMPO-based initiators [45]. Additionally, Dire et al [46] confirmed that the rate constant for β-hydrogen transfer (k βtr ) of methyl methacrylate/SG1 system was three orders of magnitude lower compared to a n-butyl methacrylate/TEMPO system.…”
Section: Level Of Control Of the Copolymerizations And The Livingnessmentioning
confidence: 99%
“…SG1-base initiators such as BlocBuilder have lower activation energy and much higher dissociation rate constant (k d ) compared to TEMPO-based initiators [45]. Additionally, Dire et al [46] confirmed that the rate constant for β-hydrogen transfer (k βtr ) of methyl methacrylate/SG1 system was three orders of magnitude lower compared to a n-butyl methacrylate/TEMPO system.…”
Section: Level Of Control Of the Copolymerizations And The Livingnessmentioning
confidence: 99%
“…In designing nitroxides for applications in NMP, much attention has been directed toward fine-tuning the nitroxide structure to lower the bond dissociation energy (BDE) of the transient Nalkoxyamines formed during the polymerization process, with the goal of running NMP at temperatures above room temperature but low enough to be compatible with complex functionality and to allow convenient industrial preparation. A number of elegant studies [52][53][54][55][56][57][58][59] have investigated the details of the kinetics of N-alkoxyamine thermal homolysis (k dissociation ) and recombination (k combination ) as it applies to NMP. In addition to kinetic considerations, the stability of the free nitroxide under the polymerization conditions is also critical.…”
Section: Introductionmentioning
confidence: 99%
“…Very significant differences in polymerization rate and control are observed in scCO 2 between SG1-alkoxyamine 1d and TIPNOalkoxyamine 1a with M n (1d) > M n (1a) and higher polydispersities for 1d than 1a (1d: M w /M n = 1.25-1.57 and 1a: M w /M n = 1.22-1.36). The higher rate and inferior control for SG1 in scCO 2 is due to a combination of higher K, 50,51 and a higher solubility of SG1 in scCO 2 , leading to greater nitroxide partitioning away from the locus of polymerization after particle formation. Although there is no literature data available for nitroxide solubilities in scCO 2 , one may expect a greater solubility for TIPNO in the organic phase (particles) due to TIPNO's organic nature in comparison to SG1, which contains heteroatoms (e.g.…”
Section: Precipitation Polymerizations In Supercritical Carbon Dioxidmentioning
confidence: 99%